2018
DOI: 10.18527/2500-2236-2018-5-1-12-21
|View full text |Cite
|
Sign up to set email alerts
|

The problem of bacterial complications post respiratory viral infections

Abstract: Every person over the course of their lifetime is repeatedly infected by a variety of respiratory viruses that represent risk factors for the development of bacterial complications. The most dangerous among the etiological factors of acute respiratory viral diseases is the influenza A virus. This virus is capable of causing catastrophic pandemics with high mortality mainly due to secondary bacterial pneumonia. As has been shown in numerous recent studies, the main mechanism of provoking bacterial infections ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 103 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…The rate of laboratory-confirmed viral-bacterial co-infection in this cohort of patients was in the lower range of the previously reported (2–77%) [ 31 , [40] , [41] , [42] , [43] , [44] , [45] ]. This is likely due to heterogeneity of our study population [46] , type of respiratory virus [ [47] , [48] , [49] ], viral detection methods [20] , case definition, community-acquired or nosocomial co-infection, seasonal variation and pandemics [ 50 , 51 ]. Moreover, we showed that laboratory-confirmed co-infection is associated with increased mortality, which is consistent with the findings from a recent meta-analysis on 31 studies consisting of 10, 762 patients with community-acquired pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of laboratory-confirmed viral-bacterial co-infection in this cohort of patients was in the lower range of the previously reported (2–77%) [ 31 , [40] , [41] , [42] , [43] , [44] , [45] ]. This is likely due to heterogeneity of our study population [46] , type of respiratory virus [ [47] , [48] , [49] ], viral detection methods [20] , case definition, community-acquired or nosocomial co-infection, seasonal variation and pandemics [ 50 , 51 ]. Moreover, we showed that laboratory-confirmed co-infection is associated with increased mortality, which is consistent with the findings from a recent meta-analysis on 31 studies consisting of 10, 762 patients with community-acquired pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…While most respiratory viruses cause pathology directly by a cytopathic effect or by triggering immune responses, a main complication of ARVIs is furthermore their ability to facilitate secondary bacterial infections, thereby provoking pneumonia, otitis, meningitis, and other acute inflammatory pathologies. In fact, ARVIs are estimated to be the primary reason for about half of the community‐acquired pneumonia cases, [ 4 ] thus also impacting on antibiotic use and occurrence of multidrug resistant bacteria.…”
Section: Introductionmentioning
confidence: 99%